Analysis on heating performance and thermal forming of lightweight alloy using pulse current heating. (2017) - Wang, B.; Yi, Z.X; Lai, X.M.; Zhang, K.F.
Abstract: Abstract: Pulse current getting through the lightweight alloy sheet could have thermal and non-thermal effects. AlLi alloy and Al MMCs materials were used to study on pulse current heating behaviors and thermal forming performance. The high-intensity pulse current flows through the sheet and generates the tremendous Joule heat. The sheet were heated to forming temperature in several second and arrived at steady state between energy input and losses. The thermal forming set-up using pulse current heating was design and the process parameters were confirmed. The results shows that the channel parts of AlLi alloy and Al MMCs materials were successfully formed and exhibited good shape retention, surface quality, and high geometry accuracy.